The Setting Presented in Trai Bhum Beliefs in the Early Rattanakosin Poetic Tales Literature (King Rama I – III) - Khwanthong, Sarinya (Journal of Buddhist Anthropology, 2022)
The objective of this research was to examine the setting presented in Trai Bhum Beliefs in the Early Rattanakosin Poetic Tales Literature (King Rama I – III) for 20 poetic tales. This research is document research that collect the setting presented in Traibhumi Katha and Traibhumi Lokavinicchayakatha to define as the scope of setting in Trai Bhum Belieffs for this study. Consequently, the setting presented in Trai Bhum Beliefs in the Early Rattanakosin Poetic Tales Literature (King Rama I – III) were analyzed which is presented through descriptive analysis paradigm. The results found that there were 10 settings derived from the concept of Trai Bhum Beliefs were found in the Early Rattanakosin Poetic Tales Literature. Those settings were 1) setting of hell realm (found in 7 tales), 2) setting of demon realm (found in 4 tales), 3) setting of human realm (found in 7 tales), 4) setting of heaven realm (found in 18 tales), 5) setting of Brahma realm (found in 4 tales), 6) setting of Nirvana (found in 5 tales), 7) setting of Himavanta (found in 14 tales), 8) setting of Mount Meru and Mount Sattaboribhan (found in 16 tales), 9) setting of River Sritandorn (found in 6 tales), and 10) setting of Chimphali (found in 2 tales). These settings were scattered in different parts of the tales and the content of these parts was rather similar. Mostly, only names of the places and things were mentioned in the settings without describing details or describes in little detail. The presented of settings from the concept of Trai Bhum Beliefs revealed the literary convention and the continuation of the belief in Trai Bhum Beliefs to remain firmly in Thai society.